2007
DOI: 10.1016/j.neuroscience.2007.02.051
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the effect of finasteride on acute ethanol withdrawal severity in C57BL/6J and DBA/2J mice

Abstract: The neurosteroid allopregnanolone (ALLO) is a potent positive modulator of γ-aminobutyric acid A (GABA A ) receptors that can modulate ethanol (EtOH) withdrawal. The 5α-reductase inhibitor finasteride can block the formation of ALLO and other GABAergic neurosteroids and also reduce certain effects of EtOH. Treatment with finasteride during chronic EtOH exposure decreased EtOH withdrawal severity and blood EtOH concentrations (BECs), suggesting an additional effect of finasteride on EtOH pharmacokinetics. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 60 publications
5
24
0
Order By: Relevance
“…In contrast, finasteride increased acute withdrawal severity in female mice of both inbred strains. With this acute ethanol procedure, pretreatment with finasteride did not alter blood ethanol concentration, nor did it alter plasma corticosterone or 17â-estradiol levels in a manner that could explain the sex difference in finasteride's effect on acute ethanol withdrawal severity (59). Overall, finasteride pretreatment produced comparable effects in the acute and chronic ethanol withdrawal models in male mice, whereas it produced opposite effects in the female mice.…”
Section: Effects Of Chronic Alcohol Exposure and Withdrawalmentioning
confidence: 75%
See 1 more Smart Citation
“…In contrast, finasteride increased acute withdrawal severity in female mice of both inbred strains. With this acute ethanol procedure, pretreatment with finasteride did not alter blood ethanol concentration, nor did it alter plasma corticosterone or 17â-estradiol levels in a manner that could explain the sex difference in finasteride's effect on acute ethanol withdrawal severity (59). Overall, finasteride pretreatment produced comparable effects in the acute and chronic ethanol withdrawal models in male mice, whereas it produced opposite effects in the female mice.…”
Section: Effects Of Chronic Alcohol Exposure and Withdrawalmentioning
confidence: 75%
“…Since the terminal elimination half-life of finasteride in the circulation in humans is 4.7 to 7.1 h (132), we presumed that the use of an acute ethanol withdrawal procedure would allow the clearance of finasteride prior to ethanol injection, reducing or eliminating this potential interaction with ethanol metabolism. Using this model, results from our laboratory suggest that pretreatment with finasteride decreased acute withdrawal severity, measured by HICs, in male C57BL/6J and DBA/2J mice (59). In contrast, finasteride increased acute withdrawal severity in female mice of both inbred strains.…”
Section: Effects Of Chronic Alcohol Exposure and Withdrawalmentioning
confidence: 90%
“…Both of these paradigms resulted in decreased body weight compared to control animals (data not shown) and increased corticosterone levels. It is unclear as to the event, ethanol exposure versus withdrawal, that precipitated the increase in corticosterone levels, as acute ethanol exposure causes an increase in corticosterone levels (Gorin-Meyer et al, 2007).…”
Section: Ethanol Exposure Paradigmmentioning
confidence: 99%
“…We have recently reported that the anticonvulsant effect of ALLO was decreased during ethanol withdrawal in male WSP mice, whereas sensitivity was unchanged in male WSR mice . Based on these data, the purpose of the present study was to examine sensitivity to the anticonvulsant effect of ALLO during ethanol withdrawal in female WSP and WSR mice, since female rodents display fewer physical symptoms of withdrawal (Devaud & Chadda, 2001;Gorin-Meyer et al, 2007;Veatch et al, 2007) and have higher circulating plasma ALLO levels than males (Finn et al, 2004b;Morrow et al, 1999;Paul and Purdy, 1992). Sensitivity to the anticonvulsant effect of ALLO during ethanol withdrawal was examined, and circulating hormone levels of progesterone, corticosterone, and estradiol were measured.…”
Section: Introductionmentioning
confidence: 99%